Effect of sound stress on ovulation, estrus, and conception in beef heifers - Heersche, G. Jr.; Kiracofe, G.; McKee, M.; Ames, D.R. (Kansas State University. Agricultural Experiment Station, 2011)
Thirty of the 50 heifers used in estrous synchronization studies and that received prostaglandin and Syncro-Mate B to synchronize estrus were subjected to sound stress for 48 hours after prostaglandin was injected. Fifty-nine percent of 29 sound-stressed heifers that showed estrus within 5 days conceived when artificially inseminated compared with 72 percent of 18 nonstressed heifers.
Keywords: Beef; Ovulation; Estrus; Conception; Heifers